Calcineurin inhibitors acutely improve insulin sensitivity without affecting insulin secretion in healthy human volunteers - Øzbay, Lara Aygen (Blackwell Science Inc, 2012)
AIM: The introduction of calcineurin inhibitors (CNIs) ciclosporin (CsA) and tacrolimus (Tac) has improved the outcome of organ transplants, but complications such as new onset diabetes mellitus after transplantation (NODAT) cause impairment of survival rates. The relative contribution of each CNI to the pathogenesis and development of NODAT remains unclear. We sought to compare the impact of CsA and Tac on glucose metabolism in human subjects. METHODS: Ten healthy men underwent 5 h infusions of CsA, Tac and saline in a randomized, double-blind, crossover study. During infusion glucose metabolism was investigated using following methods: a hyperinsulinaemic-euglycemic clamp, an intravenous glucose tolerance test (i.v.GTT), glucose-stimulated insulin concentration–time series and indirect calorimetry. RESULTS: Clamp derived insulin sensitivity was increased by 25% during CsA (P < 0.0001) and 13% during Tac administration (P = 0.047), whereas first phase and pulsatile insulin secretion were unaffected. Coinciding with the CNI induced improved insulin sensitivity, glucose oxidation rates increased, while insulin clearance rates decreased, only non-significantly. Tac singularly lowered hsCRP concentrations, otherwise no changes were observed in circulating glucagon, FFA or adiponectin concentrations. Mean blood concentrations of CNIs were 486.9 ± 23.5 µg l(−1) for CsA and 12.8 ± 0.5 µg l(−1) for Tac. CONCLUSIONS: Acute effects of i.v. CsA, and to a lesser degree Tac infusions, in healthy volunteers include increased insulin sensitivity, without any effect on first phase or pulsatile insulin secretion.